Eyes - Goode, Katherine, 1949- (Woodbridge, CT : Blackbirch Press, 2000)
Explains the functions of the different parts of the eye.
Includes index.
Science and Children (N.S.T.A.).
3.0.
3.0
3-6
Keywords: Eye -- Juvenile literature; Eye; Eye